Roteamento sensível ao contexto em redes de sensores sem fio : uma abordagem baseada em regras de aplicação para o Protocolo RPL - Antunes, Vinicius Barcellos (2014)
This work presents a dynamic reconfiguration service for wireless sensor networks. The work includes the design and definition of a conceptual architecture that supports collecting a variety of contextual information and provides a high level abstraction for context-sensitive routing specification through reconfiguration of routing metrics and communication parameters. The objective of the proposed infrastructure is enabling the creation of rules that change the network's behavior at run time, in the light of these contextual information. An implementation of the architecture for the RPL Protocol and the Contiki operating system was performed, showing the feasibility of the proposed approach.